Socioeconomic disparities in influenza vaccination uptake: impact of the COVID-19 pandemic in South Korea - Muhan Yeo; Jeongmin Seo; Juwon Lim (BMC Public Health)
Abstract Background This study aimed to investigate the sociodemographic and behavioral factors related to increased influenza vaccination uptake during the COVID-19 pandemic in South Korea, particularly among adults not eligible for free vaccination. Methods Analyzing data from 78,815 participants in the Korea National Health and Nutrition Examination Survey (2010–2021), we assessed trends in influenza vaccination coverage. Various sociodemographic factors, behavioral aspects, and psychological stress levels were assessed using multivariable logistic regression to evaluate the difference in vaccination response during pre-/post-COVID-19 periods. Results Lowest income quartile households exhibited decreased influenza vaccination uptake during the pandemic (adjusted odds ratio 0.67, p = 0.011), whereas higher income quartiles exhibited increased uptake. In the lowest income households, unemployed status of household was additionally associated with decreased influenza vaccine uptake (adjusted odds ratio 0.50, p = 0.003). Conclusions This study identified income-based disparities in the responsive increase of influenza vaccination during the COVID-19 pandemic. Lower-income households exhibited a disproportionate reduction in influenza vaccine uptake, emphasizing the need for targeted support systems and expanded free vaccination for prioritized groups to address these disparities.